Potensi Penurunan Debit Banjir di Sungai Sepaku Akibat Pembangunan Bendungan Sepaku Semoi (EXTRAPOLASI, 2023)
The high rainfall in the Sepaku DAS is one of the factors causing the flooding in the River Sepaku. The heavy rain often resulted in the flooding of residents' houses and public facilities. Less water reservoirs and unavailable sustainable drainage systems are some of the causes of flooding in the region. To address the flood problems, the government plans to build a dam to control flooding and increase the need for raw water in the Penajam Paser Utara district, especially in the Sepaku district. In line with this, research has been carried out to obtain a reduction in flood discharge due to the awakening of the Sepaku Semoi Dam. This study analyzed maximum daily rainfall data from the past decade, land cover and soil types, and flood discharge using HEC-HMS with validated results. The next step is the analysis of the flood water's high surface and the dam's area using the HEC-RAS program with 2D modeling. Modeling shows that Sepaku Semoi Dam reduces flood discharge, height, and volume. Drainage was decreased by 48,450%, flood height was lowered to 0.45 m, and volume was decreased by 5,080.8 m3. The flooded area also fell by 9,144 ha.